Common Mobile Learning Characteristics-An Analysis Of Mobile Learning Models And Frameworks - Imtinan, Umera; Chang, Vanessa; Issa, Tomayess (IADIS Press, 2013)
Mobile learning offers learning opportunities to learners without the limitations of time and space. Mobile learning has introduced a number of flexible options to the learners across disciplines and at different educational levels. However, designing mobile learning content is an equally challenging task for the instructional designers. Currently, mobile learning researchers are trying to determine a set of mobile learning characteristics to inform mobile learning design. Besides conforming to the pedagogical requirements, mobile learning instructional designers are also considering the nature of learning activities to engage learners with miniature mobile devices. Similarly, there are a number of mobile learning characteristics which are crucial to mobile learning design in order to harness the power and affordances of mobile devices as well as maintaining the learning element as the main focus. This paper is an attempt to point out common mobile learning characteristics as they appear in key mobile learning conceptualizations, models and frameworks in the literature. These characteristics may be useful for future researchers to inform the mobile learning design process as well as mobile learning conceptualizations.